Seed regulations and certification system strengthened in Afghanistan - CGIAR Research Program on Policies, Institutions, and Markets (2019)
With funding from the European Union through the project “Public-Private-Producers Partnership for Strengthening Seed Certification in Afghanistan” (2015-2019), ICARDA provided technical support to the Afghan Ministry of Agriculture, Irrigation and Livestock to develop legal and technical documents for a strengthened seed certification system.